PENGHIMPUNAN DAN PENDISTRIBUSIAN ROYALTI MUSIK INDEPENDEN DI KOTA SEMARANG - Kusumahadi, Dinar Satrio (Fakultas Hukum Universitas Islam Indonesia, 2022)
This study aims to determine the collection and distribution of royalties for indie music and songs in the city of Semarang. This type of research uses empirical legal research. The research was conducted using a sociological-policy approach. Sources of legal data are primary and secondary. The results showed that, first, the collection of royalties was carried out in three stages. The first stage is to list the places and platforms that play the works of indie musicians in the city of Semarang. The second stage is negotiation. The third stage is a site survey and signing a royalty agreement with indie musicians in Semarang whose works will be screened there. Then, the distribution of royalties is carried out in two ways, namely for screenings in public places and screenings on online platforms. Second, the legal obstacle in collecting and distributing music royalties to indie musicians in Semarang City is that many still do not know about LMKN, especially LMKN Semarang Representatives. Then, they still do not register their work with the Ministry of Law and Human Rights.